2021
DOI: 10.1186/s13287-021-02497-1
|View full text |Cite
|
Sign up to set email alerts
|

The tRNA-derived fragment 5026a inhibits the proliferation of gastric cancer cells by regulating the PTEN/PI3K/AKT signaling pathway

Abstract: Background Recently, tRNA-derived fragments (tRFs) have been shown to serve important biological functions. However, the role of tRFs in gastric cancer has not been fully elucidated. This study aimed to identify the tumor suppressor role of tRF-5026a (tRF-18-79MP9P04) in gastric cancer. Methods Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was first used to detect tRF-5026a expression levels in gastric cancer tissues and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 51 publications
0
46
0
Order By: Relevance
“…Since previous studies demonstrated tsRNAs could exert biological mechanisms in a manner similar to miRNAs by binding to the 3’-UTR of target genes, 29 we predicted target genes of tiRNA-Val-CAC-001 and explored its roles using bioinformatics method. We analyzed the target genes of tiRNA-Val-CAC-001 with GO and KEGG enrichment analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous studies demonstrated tsRNAs could exert biological mechanisms in a manner similar to miRNAs by binding to the 3’-UTR of target genes, 29 we predicted target genes of tiRNA-Val-CAC-001 and explored its roles using bioinformatics method. We analyzed the target genes of tiRNA-Val-CAC-001 with GO and KEGG enrichment analysis.…”
Section: Discussionmentioning
confidence: 99%
“…To check the influence of miR‐203a‐3p mimic/inhibitor and siMAP3K1 on the process of the cell cycle of TPC‐1 and KTC‐1 cells, cell cycle evaluation was carried out using the PI/RNase staining reagent (Becton), and were detected with a flow cytometer (Beckman Coulter) as previously described. 18 …”
Section: Methodsmentioning
confidence: 99%
“…A better understanding of tRF biomarkers may help elucidate possible biomarkers. For example, tRF-5026a was shown to regulate PTEN/PI3/AKT signaling pathway and decrease gastric cancer cell proliferation, suggesting that tRF-5026 may be used as a biomarker for gastric cancer ( Zhu et al, 2021 ).…”
Section: Trna-derived Fragments and Cancer Developmentmentioning
confidence: 99%